Transport of Ions and Solvent Through a Nafion Membrane Modified with Polypyrrole - Xu, Feina; Kameche, Mostèfa; Innocent, christophe (Journal of Membrane and Separation Technology, 2012)
The Nafion®117 membrane was modified chemically, using a conducting polymer pyrrole. The oxidants ferric chloride (PPy-Fe), hydrogen peroxide (PPy-O) and ammonium persulfate (PPy-S) were used to carry out the polymerization in the membrane both in aqueous and organic media. The Nafion® modified in the presence of the N-méthylformamide increases the transport of alkali and heavy metal cations and reduces considerably the transport of methanol both in diffusion and electro-osmosis. Therefore, the modified Nafion® membrane can be used successfully in electrodialysis of electrolyte solutions in both aqueous and hydro-organic media and may be regarded as a good material to use in Direct Methanol Fuel Cells.